Рыбы малых рек Правобережного Полесья УССР. Сообщение II. Видовой состав рыбного населения правобережных притоков среднего течения Припяти - Полтавчук, М.А. (Вестник зоологии, 1976)
The communication deals with the data on species composition, distribution and number ratio of fishes in main biotopes of the rivers Styr, Goryn, Sluch, Ubort as well as with the linear dimensions of fingerlings in those rivers and data on fry nutrition in the Styr and Goryn rivers.